Management of Causes and Impacts of Design Changes in Ethiopian Building Projects; The Case of Arsi Zone Public Building Construction Projects - Kassim, Kabeto (ASTU, 2022)
The purpose of this study is to investigate causes and impacts of design change in public buildings and Management of Causes and Impacts of Design Changes in Arsi Zone. In this study data collection tools were questionnaires, case study and group discussion on sample public building projects. From 64 questionnaires distributed, 58 were responded with response rate of 90.6%. The data were analyzed by using SPSS software version 25 and the Relative Importance Index (RII). The results revealed various factors that lead to design change in public building construction projects, such as; Additions of new works at the request of the client, Poor coordination and communication between parties, Design Errors, Willingness to use alternative materials, The desire of the contractor to improve his financial situation, Inconsistency of the contractual document, Unexpected site conditions and Design change made by consultants. From the results of RII analysis the impacts of design change on overall performance of construction projects, such as Delay of the projects, suspension of the projects and Increase of project cost. The Selected Current Design Change Management practice discussed are involvement of experienced technical personnel, involvement of end users before starting of the construction and ensure sufficient budget for the project also the Result also shows that the parameters used to develop the design change management system flowchart such as Proper supervision, involvement of end users at Design Stage, involving design team in construction process, and developing professional skill of design team were very important to develop the best design change management system flowchart. The study address the management of causes and impacts of design change in public building projects, the researcher creates a management system flowchart as a mitigation measures. The study concludes that paying a serious attention to the major causes of design change will be very important to manage the impacts and finally achieve the goals of project. The researcher recommend that always work to identify major causes of design change and properly manage the impacts of the design change happened at any time. And the researcher recommends studying on the wider area and including more construction projects for further study.
Keywords: Design change, Design Change management, Public building projects, Arsi Zone